The application of flipped classroom in foreign language education at Pesantren-based school - Moh. Najib Mubarok (Universitas Muhammadiyah Malang, 2025)
This study examines the implementation of the flipped classroom model in foreign language instruction at SMP Islam Ulul Albab, an Islamic boarding school, focusing on the challenges faced by teachers in its application in English language classes and students' attitudes towards the method. A qualitative case study approach was employed, involving semi-structured interviews, classroom observations, and asynchronous media reviews, with each participant interviewed twice, complemented by document analysis for triangulation. The study revealed three main findings: first, the flipped classroom model utilized the DDFE (Divide, Differentiate, Facilitate, Evaluate) framework and integrated project-based learning strategies, aligning with the pedagogical principles of Pesantren schools; second, teachers faced challenges such as students' lack of motivation for pre-class activities, time constraints, and limited internet access; and third, students’ attitudes towards the model were shaped by personal, educational, and social factors. Observations indicated varying student engagement, with some participating actively in collaborative discussions and project-based activities, while others struggled with self-directed learning, particularly in the context of unreliable internet access, which hindered their participation in pre-class activities. The findings highlight the need for targeted strategies to enhance student motivation for pre-class preparation and to explore alternative technological solutions in settings with limited internet resources. Additionally, understanding the complex factors influencing students' attitudes is crucial for optimizing the effectiveness of flipped classroom approaches. This study contributes to the literature on flipped learning, offering insights into its application in non-traditional educational contexts and providing practical recommendations for educators and policymakers aiming to improve foreign language instruction in similar settings.